Pengaruh Keterampilan dan Kecerdasan Emosional Terhadap Produktivitas Kerja Di Auto 2000 Plaju (Jurnal Manajemen dan Investasi (MANIVESTASI), 2021)
ABSTRACTÂ This study aims to determine the effect of skills and emotional intelligence on work productivity at AUTO 2000 Plaju. The research method used is quantitative research methods with a population of all mechanical employees at AUTO 2000 Plaju totaling 49 people. The sample used in this study using saturated sampling technique in order to obtain a sample of 49 employees. The data collection technique was carried out by observation and questionnaires. The data analysis technique used multiple linear regression, coefficient of determination, hypothesis testing t test and F test using the software program spss 23 for windows. The results of this study show that the value of the multiple linear regression equation Y = 5.740 + 0.026X1 + 1.088X2 + e. The results of the coefficient of determination show the value of R square of 0.456 or 45.6% means the contribution of the contribution of the influence of skills (X1) and emotional intelligence (X2) to work productivity (Y) of 45.6%. The results of testing the hypothesis t test skills (X1) on work productivity (Y) with a significant value of 0.461> 0.05, it can be concluded that partially there is no significant effect between skills on work productivity at AUTO 2000 Plaju. The results of testing the t test of emotional intelligence (X2) on work productivity (Y) with a significant value of 0.000